The biology, ecology and population trends of jacopever Helicolenus dactylopterus in South Africa - Weston, Laura Frances (Department of Biological Sciences, 2022)
Helicolenus dactylopterus is a deep-water benthic fish in the subfamily Sebastinae. Sebastinae species are slow-growing, long-lived and potentially vulnerable to overexploitation. Helicolenus dactylopterus is exploited throughout its Atlantic distribution. In South Africa, it is the eighth-most landed species in the demersal trawl fishery. Because little research has been conducted on H. dactylopterus locally, it is difficult to understand its response to fishing pressure. The life history, habitat preference and population trends of the species in South Africa were thus investigated. The age, growth, reproductive characteristics and diet were examined from 719 specimens collected from west and south coast trawls. The maximum age estimated was 32 years and the growth rate was low (k=0.13 year-1 ). Gamete release in both sexes was asynchronous, suggesting an unusual delay between insemination and fertilisation. Sperm storage was found in histologically analysed ovaries. The diet investigation indicated a selective benthic predator with an ontogenetic shift in diet from crustaceans to teleosts. To assess habitat preference, generalised linear models were fitted to broad and fine resolution abundance data from research trawls and video footage respectively. Trawl data indicated that H. dactylopterus primarily occurs in the Atlantic, decreasing in abundance in the Indian Ocean. Depths from 100 to 600 m were preferred, corresponding with the offshore demersal trawl footprint. Video data highlighted that H. dactylopterus, especially individuals >200 mm TL, preferred complex benthic habitat, typical of deep-water reef systems on the South African outer shelf and shelf edge. Standardised catch-per-unit-effort from trawl data indicated an increase in the abundance of H. dactylopterus from 1987 to 2001 in response to management reforms. Subsequently, a reduction in abundance occurred, but sustained population growth of 1.42% per year since 2005 suggests a national classification of the species as Least Concern against the IUCN Red List criteria. This study provides a thorough region-specific account of a previously data-limited species. Helicolenus dactylopterus shows life history traits typical of the Sebastinae, yet, in South Africa, the species has not succumbed to fishing pressure to the expected extent.